2021
DOI: 10.3390/insects12040355
|View full text |Cite
|
Sign up to set email alerts
|

Dose–Response Assay for Synthetic Mosquito (Diptera: Culicidae) Attractant Using a High-Throughput Screening System

Abstract: Natural volatile host cues play a critical role for mosquito orientation and locating a blood source for egg production. Similar olfactory activation responses have allowed the use and development of artificial chemical attractants to lure mosquitoes to trapping devices. Using a pre-formulated commercial product mixture of different attractant chemicals, a high-throughput screening system (HITSS) is used to screen varying doses of chemical required to activate behavioral responses. Two strains of Aedes aegypti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 58 publications
(76 reference statements)
1
8
0
Order By: Relevance
“…In particular, economical and simple methodologies are critical for the development of mosquito attractants in less well-equipped laboratories. Recently, Kim et al [ 22 , 23 ] evaluated a potential tool for lure development, the HITSS assay. However, more data are needed to demonstrate its accuracy in larger-scale SFS house set ups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, economical and simple methodologies are critical for the development of mosquito attractants in less well-equipped laboratories. Recently, Kim et al [ 22 , 23 ] evaluated a potential tool for lure development, the HITSS assay. However, more data are needed to demonstrate its accuracy in larger-scale SFS house set ups.…”
Section: Discussionmentioning
confidence: 99%
“…quinquefasciatus was more strongly attracted by 0.1 g of dry ice than Ae. aegypti [ 23 ]. We also found that the amounts of the lure ingredients were among the most crucial factors for mosquito attraction and repellence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although several assays have been proposed to screen mosquito attractants ( Kim et al, 2021a ; 2021b ) or repellents ( Grieco et al, 2005 ; Tisgratog et al, 2016 ; Kajla et al, 2019 ; Chauhan et al, 2021 ), creating a controlled environment to simultaneously test the impact of multiple variables such as temperature and blood type on mosquito feeding behavior remains challenging. Several recently published experimental platforms effectively quantify repellent effectiveness, but often rely on human volunteers or use spatially inefficient designs, thereby limiting their scalability ( Goodyer et al, 2020 ; Farooq et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%